Once upon a time : - Gargiulo, Terrence L. (Pfeiffer, 2007)
Once Upon a Time will show you how to develop exceptional communication skills, and it will serve as an invaluable resource for helping others do the same. Stories are a natural part of how we communicate. Yet many of us are unaware of the different ways we use stories. This book will take the intuitive aspects of communicating through stories and break it down into repeatable practices and essential competencies. The story-based activities in the second half of the book will give you powerful, easy to lead, structured, experiential exercises that can be used in a variety of settings and for lots of different purposes that go beyond training